Near‐Infrared Spectroscopy measurements are reliable for studying patellar bone hemodynamics and affected by venous occlusion, but not by skin compression - Martin J. Ophey; Anne Westerweel; Maxime vanOort; Robert van denBerg; Gino M. M. J. Kerkhoffs; Igor J. R. Tak (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose According to the homeostasis model, patellofemoral pain (PFP) results from disturbed homeostasis due to vascular insufficiency in the anterior knee. Near‐Infrared Spectroscopy (NIRS) measures relative changes in concentrations (in µmol/cm2) of (de‐)oxygenated hemoglobine (HHb and O2Hb). The aims were to: 1) investigate the characteristics of the NIRS signal derived from the patella during experiments affecting hemodynamics in healthy controls, and 2) determine the test–retest reliability of NIRS in positions clinically relevant for PFP patients. Methods Two experiments were conducted on 10 healthy controls and analysed using Student’s t‐test. Reliability (ICC2,1) was evaluated for two activities (‘Prolonged Sitting’ and ‘Stair Descent’) in five PFP patients and 15 healthy controls, performed twice within five days. Results The NIRS signal (HHb and O2Hb) showed a statistically significant increase (p < .001 –. 002) on all optodes (30, 35, 40 mm) during ‘Venous Occlusion’ (M = 1.0 – 2.0), while it showed no statistically significant change (p = .075 –. 61) during ‘Skin Compression’ (M = ‐0.9 – 0.9) on the 30 and 35 mm optode. Reliability of NIRS (HHb and O2Hb) ranged from moderate to almost perfect (ICC2,1 = .47 –. 95) on the 30 mm optode for ‘Prolonged Sitting’, and from moderate to substantial (ICC2,1 = .50 –. 68) on the 35 mm optode for ‘Stair Descent’. Conclusions Patella NIRS measurements are affected by venous occlusion, but not by skin compression, and are sufficiently reliable as research application to compare real‐time patellar bone hemodynamics. These insights may assist to improve effectiveness of evidence‐based treatment strategies for PFP. Trial registration ISRCTN Trial Registration under number: 90377123.